The Effect of K-Pop Industry on Metamorphosis of Digital Marketing Entertainment Business During Covid-19 Pandemic - Emi Destiani (International Journal Administration, Business & Organization, 2023)
The purpose of this study is to find the impact of the Covid-19 Pandemic on the metamorphosis of the digital entertainment business in the K-Pop industry. The sample used in this study amounted to 150 respondents who are fans of K-Pop in Bandung. This study used descriptive analysis, validity test, reliability test, correlation analysis and simple regression analysis. Data collection was conducted through questionnaires distributed through social media to respondents who met the criteria. In this study, the results obtained were 61,7% of the influence of K-Pop industry on digital marketing entertainment during covid-19. The results of this study indicate that K-Pop industry on digital marketing entertainment during covid-19 has influence and its influence is included in the strong criteria.